The issues and challenges of the enforcement of the laws governing the prohibition of smoking in public places in Malaysia: a comparative study with the position in Australia / Muhammad Akmal Azmi … [et al.] - Azmi, Muhammad Akmal; Mazlan, Mazuhairie Ifwat; Mohd Yoki, Nuzul Fitrie; Ishak, Muhammad Norazam (2012)
From the literature review as well as the background of this proposal, it is apparent that the question on the issues and challenges of the Control of Tobacco Product Regulations 2004 in enforcing the laws governing the prohibition of smoking in public places in Malaysia can only be effectively addressed by thoroughly examining the strengths as well the weaknesses of our current law by comparing it to the law in Australia in hope that the lacunae can be fill. There were several methods used in order to find answers and to collect facts to answer the research question and to meet the objectives of the study methodology employed in this study is qualitative method. Qualitative research is conducted on is a library based research as well as fieldwork. Library based research is done by examining the primary sources which is the provisions in the Control of Tobacco Product Regulations 2008 which is under the parent act of Food Act 1983 and also obtaining the secondary sources such as journals, articles, government publications, books written on similar issues, internet sources and online database such as lexis-nexis, MLJ and also CLJ law. Semi-structured interviews will be conducted on selected individuals whom are very wellverse in the relevant area of law namely in the Local Health Officer, Mohd Rizal Bin Rusuli, Penolong Pegawai Kesihatan Persekitaran U32 and the Local Municipal, Muhammad Hafiz Bin Hamid, Legal Officer of Majlis Bandaraya Shah Alam (MBSA). This method gives us the opportunity to obtain opinions and suggestions of the relevant individuals and thus, maintains the originality of our research proposal.